2018
DOI: 10.1007/s13730-018-0359-5
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypermagnesemia induced by magnesium oxide ingestion: a case series

Abstract: Hypermagnesemia is generally considered an exceptional iatrogenic condition usually caused by magnesium-containing cathartics. In particular, this condition often develops when magnesium-containing cathartics are administered to elderly patients with renal insufficiency or bowel movement dysfunction. Although magnesium oxide (MgO) is widely prescribed as a laxative, serum magnesium concentration has not been examined in most cases. In this report, we present the cases of four elderly patients with constipation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…High CKD, greater age, and long-term use of magnesium oxide were shown to be risk factors for hypermagnesemia. (3,(5)(6)(7)(8)(9)(10) Most of these studies, however, were case reports or studies of certain groups, including elderly patients, children, and patients undergoing hemodialysis. The results of the present retrospective cohort study showed that reduced renal function was the most important risk factor for hypermagnesemia and high serum magnesium concentration in patients taking magnesium oxide for functional constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High CKD, greater age, and long-term use of magnesium oxide were shown to be risk factors for hypermagnesemia. (3,(5)(6)(7)(8)(9)(10) Most of these studies, however, were case reports or studies of certain groups, including elderly patients, children, and patients undergoing hemodialysis. The results of the present retrospective cohort study showed that reduced renal function was the most important risk factor for hypermagnesemia and high serum magnesium concentration in patients taking magnesium oxide for functional constipation.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Prolonged treatment with magnesium oxide, however, may induce hypermagnesemia. (4)(5)(6)(7)(8)(9) Serum magnesium concentrations >5.0 mg/dl have been associated with nausea, headache, light-headedness, and cutaneous flushing, whereas levels above 12 mg/dl have been associated with respiratory failure, complete heart blockage, and cardiac arrest. (10) Recently, the Japanese Ministry of Health, Labour and Welfare recommended that serum magnesium concentrations be measured periodically in geriatric patients and in patients administered magnesium oxide for prolonged periods of time (http://www.pmda.…”
mentioning
confidence: 99%
“…Many reports have described the treatment of hypermagnesemia with hemodialysis [1-3, 5-7, 9, 12, 13]. However, few reports have described hypermagnesemia in patients with normal renal function [1,5,[7][8][9], and even fewer reports have described severe hypermagnesemia that improved with symptomatic treatment alone [7]. In our case, serum Mg levels in the patient normalized without hemodialysis.…”
Section: Discussionmentioning
confidence: 60%
“…Intravenous infusion of normal saline and loop diuretics enhances Mg excretion in patients with normal renal function [3]. In particular, loop diuretics inhibits Mg reabsorption in the thick ascending limb of Henle's loop [8]. Hemodialysis is necessary for patients with renal failure and life-threatening symptoms [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation